Strategi Pemasaran Produk Skincare Somethinc Di Kalangan Generasi Z - Permana, Erwin; Eka Putri, Rizqi Septiani; Alfinda, Permata Diva; Mardhiyah, Muna (Jurnal Pemasaran Kompetitif, 2024)
Along with the development of the beauty product industry, many quality local skincare brands have emerged that are not inferior to skincare products from abroad. Many local brands have developed formulas and ingredients suitable for skin types and climatic conditions in Indonesia, so they can compete with skincare products from other countries. In fact, it is not uncommon for new beauty products to appear to immediately become popular in the community. This is inseparable from the role of the right marketing strategy. This study aims to analyze the marketing strategy for skincare products somethink among generation z. This study uses a descriptive qualitative methodology. Sources of data from this study are primary data and secondary data. Primary data is data obtained or collected directly by researchers by observing and interviewing Somethink consumers, while secondary data is obtained by searching various popular official sites on the internet as well as the results of previous scientific research. The results of the study show that Somethink uses a marketing mix consisting of four elements, namely product, price, place, and promotion, and develops the promotion strategy with the 5A customer path concept consisting of aware, appeal, ask, act, and advocate. In terms of promotion, Something has succeeded in attracting consumers' attention through creative and various promotional strategies. Somethinc collaborates with Han So Hee, NCT Dream, Lifni Sanders, Sabrina, Hello Kitty, Shinchan x Tahilalats, and Kopi Kenangan which is popular among Generation Z. Not only that, Somethinc is also loyal to its consumers by providing price discounts and bundling packages at low prices. affordable.